Identification of a novel WAS mutation in a South African patient presenting with atypical Wiskott-Aldrich syndrome: a case report - Brigitte Glanzmann; Marlo Möller; Mardelle Schoeman; Michael Urban; Paul D. van Helden; Lisa Frigati; Ravnit Grewal; Hermanus Pieters; Ben Loos; Eileen G. Hoal; Richard H. Glashoff; Helena Cornelissen; et al. (BMC, 2020)
Abstract Background The X-linked recessive primary immunodeficiency disease (PIDD) Wiskott-Aldrich syndrome (WAS) is identified by an extreme susceptibility to infections, eczema and thrombocytopenia with microplatelets. The syndrome, the result of mutations in the WAS gene which encodes the Wiskott-Aldrich protein (WASp), has wide clinical phenotype variation, ranging from classical WAS to X-linked thrombocytopaenia and X-linked neutropaenia. In many cases, the diagnosis of WAS in first affected males is delayed, because patients may not present with the classic signs and symptoms, which may intersect with other thrombocytopenia causes. Case presentation Here, we describe a three-year-old HIV negative boy presenting with recurrent infections, skin rashes, features of autoimmunity and atopy. However, platelets were initially reported as normal in numbers and morphology as were baseline immune investigations. An older male sibling had died in infancy from suspected immunodeficiency. Uncertainty of diagnosis and suspected severe PIDD prompted urgent further molecular investigation. Whole exome sequencing identified c. 397 G > A as a novel hemizygous missense mutation located in exon 4 of WAS. Conclusion With definitive molecular diagnosis, we could target treatment and offer genetic counselling and prenatal diagnostic testing to the family. The identification of novel variants is important to confirm phenotype variations of a syndrome.